An investigation of the mechanisms for strength gain or loss of geopolymer mortar after exposure to elevated temperature - Pan, Z.; Sanjayan, J.; Rangan, Vijaya (Springer, Netherlands, 2009)
When fly ash-based geopolymer mortars were exposed to a temperature of 800 °C, it was found that the strength after the exposure sometimes decreased, but at other times increased. This paper shows that ductility of the mortars has a major correlation to this strength gain/loss behaviour. Specimens prepared with two different fly ashes, with strengths ranging from 5 to 60 MPa, were investigated. Results indicate that the strength losses decrease with increasing ductility, with even strength gains at high levels of ductility. This correlation is attributed to the fact that mortars with high ductility have high capacity to accommodate thermal incompatibilities. It is believed that the two opposing processes occur in mortars: (1) further geopolymerisation and/or sintering at elevated temperatures leading to strength gain; (2) the damage to the mortar because of thermal incompatibility arising from non-uniform temperature distribution. The strength gain or loss occurs depending on the dominant process.